2006
DOI: 10.1055/s-2005-916219
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomised, Open, Uncontrolled, Clinical Study of Two Dosages of St John’s Wort (Hypericum perforatum) Herb Extract (LI-160) as an Aid to Motivational/Behavioural Support in Smoking Cessation

Abstract: There is an association between smoking and depression, yet the herbal antidepressant St John's wort (Hypericum perforatum L.; SJW) herb extract has not previously been investigated as an aid in smoking cessation. In this open, uncontrolled, pilot study, 28 smokers of 10 or more cigarettes per day for at least one year were randomised to receive SJW herb extract (LI-160) 300 mg once or twice daily taken for one week before and continued for 3 months after a target quit date. In addition, all participants recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…Antidepresan ve antipsikotikler, madde bağımlılarının yoksunluk sendromu tedavisinde kullanılmaktadır (6)(7)(8). Fakat bizim olgularımızda görüldüğü gibi hastaların ilaca toleransı arttıkça tedavi için aldıkları ilaca bağımlılıkları gelişmekte ve giderek artan dozlarda ve farklı yöntemlerle kullanmaktadırlar.…”
Section: Discussionunclassified
“…Antidepresan ve antipsikotikler, madde bağımlılarının yoksunluk sendromu tedavisinde kullanılmaktadır (6)(7)(8). Fakat bizim olgularımızda görüldüğü gibi hastaların ilaca toleransı arttıkça tedavi için aldıkları ilaca bağımlılıkları gelişmekte ve giderek artan dozlarda ve farklı yöntemlerle kullanmaktadırlar.…”
Section: Discussionunclassified
“…27 In another study among 28 smokers who received SJW herb extract either 300 mg once a day or 300 mg twice daily taken for 1 week before and continued for 3 months after a TQD, the point prevalence and continuous smoking abstinence rate were both 18% at 3 months. 28 Fifteen (15) participants (54%) reported adverse events, mainly gastrointestinal. This study concluded that SJW plus individual behavioral support was unlikely to be an effective aid for smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies with SJW for smoking cessation contained differing amounts of the active ingredient. 9,28 The present study used a dose of SJW with 0.3% hypericin. Different concentrations of the medication across different studies may influence the efficacy.…”
Section: Trial Of St John's Wort For Smoking Cessationmentioning
confidence: 99%
“…Les plantes actives sur le système sérotoninergique seront utiles sur les troubles mineurs de l'humeur mais aussi pour contrôler les pulsions alimentaires fréquentes dans un sevrage tabagique. C'est le cas du classique millepertuis Hypericum perforatum qui agit comme un inhibiteur de la recapture de la sérotonine, de la noradrénaline et de la dopamine au niveau du système nerveux central, grâce probablement à l'action de l'hyperforine [6,36,42]. Le millepertuis, d'utilisation délicate en raison de ses multiples interactions médicamenteuses via la voie des cytochromes P450, sera à réserver aux troubles de l'humeur de type dépression mineure apparaissant au cours de l'arrêt du tabac.…”
Section: Mé Thodes De Sevrage éValué Es Et Validé Es Quelle Efficaciunclassified